2018
DOI: 10.1002/adsu.201800076
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Stability of an RT‐NaS Battery via In Situ Electrochemical Formation of Protective SEI on a Sulfur–Carbon Composite Cathode

Abstract: lower than that of lithium. [3][4][5] Therefore, sodium has been considered appropriate for large-scale EESs as an alternative to lithium. Among the EESs using sodium, the high temperature sodium-sulfur battery (HT-NaS battery) is best known and operates at 300-350 °C with a molten electrode and a ß″-alumina solid electrolyte. At present, this technology is commercialized for stationary-energy-storage systems because of its reasonable energy density and cost. [6] However, the HT-NaS battery has limited capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Figure d displays the F 1s spectra of the discharged cathode in the FEC-containing electrolyte. The prominent peak at 684.5 eV corresponds to sodium fluoride (NaF). , The other three peaks at ∼685.9, 688.3, and 689.7 eV indicate the C–F in the decomposition products of FEC. Figure e shows the O 1s spectra, the intensity of the peaks that correspond to the NaCO 3 and alkyl carbonate of ROCO 2 Na at 532–532.8 eV and R–ONa at 533.7 eV increase with the addition of FEC in the electrolytes. , Consistently, the same tendency also appears in the C 1s spectra that NaCO 3 and ROCO 2 Na at ∼290 eV and O–CO at ∼288.5 eV get intensified with the FEC additive (Figure f) .…”
Section: Resultsmentioning
confidence: 99%
“…Figure d displays the F 1s spectra of the discharged cathode in the FEC-containing electrolyte. The prominent peak at 684.5 eV corresponds to sodium fluoride (NaF). , The other three peaks at ∼685.9, 688.3, and 689.7 eV indicate the C–F in the decomposition products of FEC. Figure e shows the O 1s spectra, the intensity of the peaks that correspond to the NaCO 3 and alkyl carbonate of ROCO 2 Na at 532–532.8 eV and R–ONa at 533.7 eV increase with the addition of FEC in the electrolytes. , Consistently, the same tendency also appears in the C 1s spectra that NaCO 3 and ROCO 2 Na at ∼290 eV and O–CO at ∼288.5 eV get intensified with the FEC additive (Figure f) .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Lee and co‐workers found that FEC additive formed a protective CEI layer on the C/S cathode, suppressing the dissolution of polysulfides. [ 67 ] The FEC‐assisted CEI layer had a thickness of ≈20 nm and contained fluoride anions that improved the cell's electrical conductivity and mechanical stability. As is well known, dissolved polysulfides undergo severe side reactions with carbonate ester solvents.…”
Section: Electrolytes For Rt Na–s Batteriesmentioning
confidence: 99%
“…Meanwhile, this passivated layer is helpful to suppress the polysulfide dissolution, leading to greatly enhanced stability and reversible capacity. [ 67 ]…”
Section: Interphase and Separatormentioning
confidence: 99%
See 1 more Smart Citation
“…The energy storage mechanism for all metal-sulfur batteries follows a conversion type mechanism [13,[150][151][152][153][154]. A simple version of this reaction occurs for lithium, sodium and magnesium [151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166]. In this mechanism the sulfur in the cathode is reduced and forms a metal sulfide complex with the metal ions from the electrolyte solution, as in Equation 22.…”
Section: Metal-sulfur Batteriesmentioning
confidence: 99%